Anonymous Secure Communication in Wireless Mobile Ad-Hoc Networks - Rahman, Sk. Md. Mizanur; Inomata, Atsuo; Okamoto, Takeshi; Mambo, Masahiro; Okamoto, Eiji (Ubiquitous Convergence Technology, 2007)
The main characteristic of a mobile ad-hoc network is its infrastructure-less, highly dynamic topology, which is subject to malicious traffic analysis. Malicious intermediate nodes in wireless mobile ad-hoc networks are a threat concerning security as well as anonymity of exchanged information. To protect anonymity and achieve security of nodes in mobile ad-hoc networks, an anonymous on-demand routing protocol, termed RIOMO, is proposed. For this purpose, pseudo IDs of the nodes are generated considering Pairing-based Cryptography. Nodes can generate their own pseudo IDs independently. As a result RIOMO reduces pseudo IDs maintenance costs. Only trust-worthy nodes are allowed to take part in routing to discover a route. To ensure trustiness each node has to make authentication to its neighbors through an anonymous authentication process. Thus RIOMO safely communicates between nodes without disclosing node identities; it also provides different desirable anonymous properties such as identity privacy, location privacy, route anonymity, and robustness against several attacks.